DAMPAK PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI)Â DINI PADA BAYI USIA 0-6 BULAN DI DESA SUMBERJATI - Ratnaningsih, Tri; Anama, Riza (JURNAL KEPERAWATAN SEHAT, 2015)
Food addition of breast milk (MP ASI) is a addition food given to babies after aged 6 months to 24 months. If babies get food in addition to breast milk too early it will increase the risk of diarhea diseases, allergies, weight gain / obesity, the frequency of drinking milk decreased. At the time of 0-6 months old baby exactly just need nutrition to breastfeeding, to obtain optimal growth and development of breastfeeding for 6 months is recommended. The research objective was to determine the impact of giving food addition early aged 0-6 months in Sumberjati village. The used method is descriptive. Population 21 people taken all with total sampling. The variable impact of giving food addition early. Data was collected using a checklist instrument. The data have been obtained and analyzed by process of editing, coding, scoring, tabulating further processed statistically with the presentation in the form of a frequency distribution table. The results showed most of the impact of giving food addition early in babies aged 0-6 months are weight gain / obesity as many as 12 respondent (37.5%). Provision of complementary foods in infants aged 0-6 months causing weight gain / obesity are not in accordance with age so that it can affect the growth and development of the babys physical and psychological. To alleviating the impact of giving food addition early, is precise information about the schedule of giving food addition and the impact of the giving food addition.Keywords: impact of giving food addition, babies aged 0-6 months